1998
DOI: 10.1017/s0954394500001277
|View full text |Cite
|
Sign up to set email alerts
|

Was/werevariation across the generations: View from the city of York

Abstract: In this article, I describe a new research project on York English (YrkE), a variety in northeast England. In addition to providing the first systematic linguistic documentation of YrkE, I conduct a quantitative analysis of a linguistic feature which not only is well documented in the literature, but also recurs pervasively in varieties of English worldwide-was/were variation in the past tense paradigm. Two separate tendencies are observed, neither of which can be explained by any unidimensional notion of anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
152
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 16 publications
8
152
1
1
Order By: Relevance
“…As for the negative ones, it seems that tags instigate the presence of weren't, especially in the speech of the elder informants where the appearance of the phenomenon under discussion is solely reserved to tags. Furthermore, tags are also crucial in the appearance of the negative allomorph in the speech of youngsters -to some extent it corroborates the results of previous research, for instance Tagliamonte's (1998), which state that tags do contribute to the overall increase of the tendency toward weren't leveling.…”
Section: Regional British Dialectssupporting
confidence: 87%
See 1 more Smart Citation
“…As for the negative ones, it seems that tags instigate the presence of weren't, especially in the speech of the elder informants where the appearance of the phenomenon under discussion is solely reserved to tags. Furthermore, tags are also crucial in the appearance of the negative allomorph in the speech of youngsters -to some extent it corroborates the results of previous research, for instance Tagliamonte's (1998), which state that tags do contribute to the overall increase of the tendency toward weren't leveling.…”
Section: Regional British Dialectssupporting
confidence: 87%
“…In a recent study on was/were variation in the city of York, Tagliamonte (1998) found that leveling to were was largely confined to negative constructions, even though it scored much lower than in the Ocracoke brogue. According to Tagliamonte (1998: 164), the conditioning factors for nonstandard weren't usage are "polarity" and "grammatical person": in fact, her results re-13 This is the exact opposite of the "subject-type constraint" also known as the "Northern subject rule" in a British context (Britain 2002), according to which nonstandard was is more likely to occur with noun subjects rather than pronoun subjects.…”
Section: Regional British Dialectsmentioning
confidence: 96%
“…For the first of these constraints, polarity, location-specific patterns have been found. For instance, Tagliamonte (1998) indicates that the presence of sentence negation disfavors the absence of agreement. This is also the effect that is generally documented in the U.S. (Tagliamonte & Baayen 2012), but in New Zealand English polarity does not seem to constrain the variation (Hay & Schreier 2004).…”
Section: (9)mentioning
confidence: 99%
“…Furthermore, these studies examine nonstandard rather than standard varieties and they may differ considerably in the frequency of the tokens collected, which may range from 29 (Cornips, 1998) to 6809 (Tagliamonte, 1998). It appears that both a low and high frequency of (morpho)syntactic variables may reveal significant correlations between the use of linguistic variants and social dimensions in the speech community.…”
Section: Variable Rule/linguistic Variablementioning
confidence: 99%